A non-traditional veterinary career: My experience as a USDA veterinarian - Ritzmann, Kathleen (My University, 2008)
One of the purposes of the summer internship experience was to discover non-traditional careers for veterinarians within the federal government. A significant amount of time was spent interviewing and talking to people in different career fields about their path to their careers as well as their role as a veterinarian in the federal government. Those areas visited included: DHS, Food, Agriculture, and Veterinary Defense; DHS, Joint Agro-Defense Office; Executive Office of the President, Office of Science and Technology Policy; FDA, Center for Food Safety and Nutrition; FDA, Center for Veterinary Medicine; National Association of Federal Veterinarians; NIH, Division of Veterinary Resources; United States Public Health Service; USDA, Animal Care; USDA, Cooperative State Research, Education, and Extension Service; USDA, Homeland Security Office; USDA, Maryland/Delaware/D.C. Area Office; USDA, National Center for Import and Export; USDA, National Veterinary Stockpile; USDA, Plant Protection and Quarantine;
Keywords: Federal government; USDA; Veterinary Service; Avian influenza; Career opportunities; Disease outbreak standard operating procedure; Biology, Veterinary Science (0778)